Analisis Rasio Kecukupan Modal dan Biaya Operasional Pendapatan Operasional Kinerja Profitabilitas PT. BNI, Tbk Tahun 2015 – 2019 - Muyasaroh Muyasaroh (STIE Amkop Makassar, 2022)
The purpose of this study was to find out how the analysis of the Capital Adequacy Ratio on profitability performance, to find out how the analysis of operating costs of operating income ( BOPO ) on profitability performance, to find out how the analysis of the Capital Adequacy Ratio and the Bopo to profitability performance. The method used in this research is to collect data from financial statements. This study uses data from 2015-2019. The type of data collected is secondary data. The results of this study explain that the Capital Adequacy Ratio in 2015 was 146.1%, in 2016 it was 62.3%, in 2017 it was 62.1%, in 2018 it was 46.4%, in 2019 it was 59. 4%, the ratio of operating expenses to operating income in 2015 was 46.8%, in 2016 it was 46.5%, in 2017 it was 46.1%, in 2018 it was 44.7%, in 2019 it was 45, 5%., Return On Assets in 2015 was 2.25%, in 2016 it was 2.37%, in 2017 it was 2.42%, in 2018 it was 2.45%, in 2019 it was 2.29%.